An Extension of Subgradient Method for Variational Inequality Problems in Hilbert Space. (12th March 2013) - Wang, Xueyong; Li, Shengjie; Kou, Xipeng
Abstract : An extension of subgradient method for solving variational inequality problems is presented. A new iterative process, which relates to the fixed point of a nonexpansive mapping and the current iterative point, is generated. A weak convergence theorem is obtained for three sequences generated by the iterative process under some mild conditions.